2016
DOI: 10.3906/zoo-1508-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the chromosome banding patterns in three species of social voles (Microtus irani karamani, M. schidlovskii, M. anatolicus) from Turkey

Abstract: The karyotypes of three species of social voles recently discovered in Turkey (Microtus irani karamani, M. schidlovskii, and M. anatolicus) were investigated. All specimens examined revealed similar karyotypes comprising 60 chromosomes in the diploid complement. All autosomes and the X chromosome were acrocentric. The subtelocentric Y chromosome was recorded in M. anatolicus but it was acrocentric in the other species. Dark C-bands were observed in centromeric/pericentromeric areas of all the acrocentric autos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…This led to interspecific variability in the chromosomal distribution and number of copies of repeats. The result of the present work tested previously mentioned hypotheses on the particular lability of the arvicoline sex chromosomes in relation to C-band www.nature.com/scientificreports/ modification 60 and also suggests a significant heterogeneity of the heterochromatic regions of the X chromosomes of voles [46][47][48][49][50]60 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This led to interspecific variability in the chromosomal distribution and number of copies of repeats. The result of the present work tested previously mentioned hypotheses on the particular lability of the arvicoline sex chromosomes in relation to C-band www.nature.com/scientificreports/ modification 60 and also suggests a significant heterogeneity of the heterochromatic regions of the X chromosomes of voles [46][47][48][49][50]60 .…”
Section: Discussionsupporting
confidence: 85%
“…C-banding of the chromosomes of most of the species used in the study was previously performed [46][47][48][49][50] . Here, in addition to T. savii, we carried out C-banding of chromosomes of six more species of voles (A. mujanensis, Alticola tuvinicus, Blanfordimys juldaschi, M. dogramacii, T. daghestanicus, and T. majori), which allowed to visualise not only centromeric, but interstitial heterochromatic blocks on X chromosomes of four of these species-A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate support (bp = 72) could be due to the underrepresentation of the former taxon with only one available sequence, thus until more data can be included the specific rank of M. i. karamani is uncertain . However, recent studies showed a much wider distribution of the latter than originally thought (Taurus Mt., Turkey; Kryštufek et al, ), as it is now found in Armenia (Golenishchev et al, ; Zorenko et al, ), eastern Iran (Mahmoudi et al, ), western and southwestern Turkey (Arslan, Toyran, Gözütok, Yorulmaz, & Zima, ; Yiğit et al, , ), and Lebanon (Kryštufek, Abi‐Said, & Hladnik, ).…”
Section: Discussionmentioning
confidence: 92%
“…It is very difficult to morphologically distinguish the Microtus, which is represented by 65 species, from each other (Musser and Carleton, 1993;Jaarola et al, 2004). However, they are frequently used in comparative cytotaxonomy studies since they differ from each other in terms of diploid chromosome numbers (2n=17-62) despite their morphological similarities (Zima and Král, 1984;Modi, 1987;Zagorodnyuk, 1990;Lemskaya et al, 2010) Turkey (Jaarola et al, 2004;Kryštufek and Vohralik, 2005;Kryštufek et al, 2012;Arslan et al, 2016;Selçuk and Kefelioğlu, 2018;Demirtaş and Gürler, 2019). These species distributed in Turkey are classified in three main groups as 'pine voles', 'social voles' and 'arvalis group' (Kryštufek and Vohralik, 2005).…”
Section: Introductionmentioning
confidence: 99%